Rising Wage Dispersion, After All ! The German Wage Structure at the Turn of the Century - Karsten Kohn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Using register data from the IAB employment sample, this paper studies the wage structure in the German labor market throughout the years 19922001. Wage dispersion has generally been rising. The increase was more pronounced in East Germany and occurred predominantly in the lower part of the wage distribution for women and in the upper part for men. Censored quantile wage regressions reveal diverse age and skill patterns. Applying Machado/Mata (2005)-type decompositions I conclude that differences in the composition of the work force only had a small impact on the observed wage differentials between East and West Germany, but changes in the characteristics captured better parts of the observed wage changes over time.
Keywords: J31; C24; 330; Wage inequality; censored quantile regression; Machado/Mata decomposition; IABS; East Germany; West Germany; Lohnstruktur; Lohndifferenzierung; Deutschland; Alte Bundesländer; Neue Bundesländer